Microarray and Bioinformatics Analysis of Circular RNA Differential Expression in Newborns With Acute Respiratory Distress Syndrome - Zhou, Huan; Chanda, Bwalya; Chen, Yu-fei; Wang, Xue-juan; You, Ming-yu; Zhang, Yi-han; Cheng, Rui; Yang, Yang; Chen, Xiao-qing (Frontiers in Pediatrics, 2021)
Previous researches pointed out that a variety of microRNAs are involved in the pathogenesis of neonatal acute respiratory distress syndrome (NARDS) and play different roles in the pathological process. However, there have been no articles reporting the connection between Cyclic RNA (circRNA) and NARDS, so the expression profile of circRNAs in newborns with acute respiratory distress syndrome remains largely unknown. In the present study, 10 samples obtained from newborns hospitalized in neonatal intensive care units (NICUs) of the First Affiliated Hospital of Nanjing Medical University from January 2020 to October 2020 were divided into ‘NARDS’ group and ‘non- NARDS’ group according to the Montelux standard and then were analyzed in microarray. circRNA expression profiles, which 741 circRNAs were downregulated and 588 were upregulated, was screened with circRNA high-throughput sequencing. Subsequently, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analysis of parent genes of the differentially expressed circRNAs revealed that these circRNAs may be related to the process of protein synthesis and metabolism in NARDS. Moreover, 5 circRNAs including hsa_circ_0058495, hsa_circ_0000367, hsa_circ_0005389, hsa_circ_0059571, hsa_circ_0006608 were selected randomly among top 10 circRNAs of the downregulated or upregulated expression profiles. Then, bioinformatics tools were used to predict correlative miRNA and its target genes, which were also subjected to the same bioinformatics analysis for further study. The top 30 enriched KEGG pathways analysis of the 125 target genes suggested that these target genes are widely involved in the synthesis and secretion of endocrine hormone, and the top 30 enriched GO terms based on the 125 target genes are also focused on the protein and DNA processing. Thus, the present results show that circRNAs could promote the inflammation of NARDS which may provide a new therapeutic direction and it can be used as molecular markers for early diagnosis of NARDS, but further molecular biology verification is needed to define the specific role of differentially expressed circRNAs in NARDS.